Characterisation of different one-stage blower configurations using 3D unsteady numerical flow simulations - Kalmár, L.; Janiga, G.; Soltész, L. (НТУ "ХПІ", 2012)
This paper deals with the CFD investigation of the flow in a one-stage radial flow blower-aggregate. The main aim of this numerical study is to compute the relevant operating characteristics of the blower-aggregate and to determine detailed information about the flow characteristics inside it. The distributions of these flow characteristics in the blower determined by the commercial code ANSYS-FLUENT [1] are available to judge whether the elements of the blower are working properly, or not. The calculated characteristics of operating parameters are compared in this paper with measured data given by experimental tests of the blower-aggregate for their validation [2]. The blower-aggregates investigated numerically are noted by BA₁, BA₂ and BA₃ in this paper.